A Baltic odyssey : war and survival - Von Rosen, Martha, 1904- (University of Calgary Press, 1995)
Fifty years after the end of World War II, two unique narratives chronicle the final months of that desperate struggle in very personal and explicit terms. While cruelly separated from one another, Jurgen and Martha von Rosen have written two parallel accounts about the same years. Baron von Rosen's prisoner-of-war diary is a standing testimonial to the horrors of imprisonment. It reveals a picture of the "enemy," and the conduct of the Allied forces toward their captives, which may be quite foreign to conventional knowledge. The Baron who had been conscripted into the Afrika Korps, was captured by the Allies in Italy after Germany surrendered in 1945. Baroness von Rosen's memoir is a refugee's account of war. As a young woman fleeing from the advancing Russians, she travelled through a harsh winter landscape accompanied by her aged parents and her young children